Pembelajaran Interaktif Materi PAI Pada Kurikulum Merdeka di MIN 5 Ngawi - Syarifah; Zuhrotul Mufidah; Nur Indah Sari; Umma Fatayati; Wahyuning Tyas Islami (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the implementation of interactive learning in Islamic Religious Education (PAI) subjects under the Independent Curriculum at MIN 5 Ngawi. The Independent Curriculum, which will be implemented nationally in 2024, emphasizes flexibility, contextual learning, and strengthening student character. This study used a qualitative approach with data collection techniques through observation, interviews, and documentation. The results show that the application of interactive learning methods—such as discussions, project-based learning, contextual learning, storytelling, and demonstrations—has proven effective in increasing student motivation and understanding of PAI materials. However, the implementation of interactive learning at MIN 5 Ngawi still faces several obstacles, including limited learning time, logistical constraints, lack of teacher training, and difficulties in integrating information technology. Furthermore, the diversity of student backgrounds demands an inclusive, multicultural approach. Nevertheless, various efforts have been made to optimize PAI learning, including through method diversification, development of learning media, teacher training, and ongoing evaluation. This study recommends the need to strengthen teacher capacity, provide adequate learning resources, and develop an inclusive and adaptive curriculum to meet student needs. Keywords: Interactive Learning, Islamic Religious Education, Independent Curriculum.